Rethinking the role of sham TMS - Duecker, Felix; Sack, Alexander T. (Frontiers in Psychology, 2015)
Sham TMS approaches are widely used in basic and clinical research to ensure that observed effects are due to the intended neural manipulation instead of being caused by various possible side effects. We here critically discuss several methodological aspects of sham TMS. Importantly, we propose to carefully distinguish between the placebo versus sensory side effects of TMS. In line with this conceptual distinction, we describe current limitations of sham TMS approaches in the context of placebo effects and blinding success, followed by a short review of our own work demonstrating that the sensory side effects of sham TMS are not unspecific as often falsely assumed. Lastly, we argue that sham TMS approaches are inherently insufficient as full-fledged control conditions as they fail to demonstrate the specificity of TMS effects to a particular brain area or time point of stimulation. Sham TMS should therefore only complement alternative control strategies in TMS research.